Are modern economies following a sustainable energy consumption path? - Recalde, Marina Yesica (2014)
In the frame of an enhanced environmental discussion regarding the existence and convenience of energy decoupling or dematerialization, this paper studies the past trends of global primary energy resources in relation to monetary and demographic variables in a top-down framework. This paper aims at contributing to the literature on dematerialization and energy sustainability from a dynamic perspective, with the purpose of shedding light on some questions, such as the real existence of an intergenerational energy dematerialization. To this purpose we use the phase diagrams of energy intensity and the product generational dematerialization (PGD) indicator for the period 1970-2011 for the global economy, the OECD and Latin American and Caribbean regions, China and India. While from energy intensity perspective a decoupling trend can be observed, we found no evidence for global intergenerational sustainable energy path in the long term. In this context, some questions related to the real impact of past and future environmental policies on energy consumption arise, especially in relation to developing countries.